TRADEMARKS AND SENSORY STIMULUS: how smells, tastes, sounds, shapes and other sensory characteristics can help to reinforce the connection between brands and consumers - Franco Brazílio, Thiago; del Vechio, Gustavo Henrique (Revista Interface Tecnológica, 2020)
New brands appear frequently in the market, further saturating the segments and, as a consequence, increasing competition, which is no small feat. Given this, brands need to find mechanisms to stand out and continue to gain the attention and trust of their stakeholders. In this way, this study seeks to better understand the importance of communications for commercial brands and how experiences that include tastes, smells, sounds, shapes, textures and other sensory characteristics can contribute to the recall of brands, products and services. In order to evaluate these concepts in practice, the study proposes a quantitative research, in which 100 consumers offer interesting opinions about the influence of sensory aspects regarding the connection they have with the brands they use. What can be seen from this work is that the more a brand invests in sensory stimuli, the more opportunities it has to stand out and be remembered much more easily by the consumer audience.